Characterization of imprinted microbeads synthesized via minisuspension polymerization - Torres, Juan Jose (2012)
The properties of MIPs synthesized by minisuspension polymerization are studied. The template is cyclododecyl 2,4-dihydroxybenzoate (1), which behaves as good mimic of the estrogenic mycotoxin zearalenone. 2-DAEM and EGDMA are used as functional and crosslinker monomers, respectively. The synthesized particles are characterized by optical and electronic microscopy, N2 sorption measurements, and FT-IR spectroscopy. The molecular recognition capability of MIPs is evaluated by comparing the adsorption Freundlich isotherms of MIPs to those of the corresponding non-imprinted polymers. It is concluded that MSP is an attractive alternative for molecular imprinting because it is easy to apply and produces high yield of spherical particles of tunable size with acceptable molecular recognition capabilities.